Organic Molecules from Biochar Leacheates Have a Positive Effect on Rice Seedling Cold Tolerance - Yuan, Jun; Meng, Jun; Liang, Xiao; E, Yang; Yang, Xu; Chen, Wenfu (Frontiers in Plant Science, 2017)
Biochar is known to have a number of positive effects on plant ecophysiology. However, limited research has been carried out to date on the effects and mechanisms of biochar on plant ecophysiology under abiotic stresses, especially responses to cold. In this study, we report on a series of experiments on rice seedlings treated with different concentrations of biochar leacheates (between 0% and 10% by weight) under cold stress (10 °C). Quantitative real-time PCR (qRT-PCR) and cold-resistant physiological indicator analysis at low temperatures revealed that the cold tolerance of rice seedlings increased after treatment with high concentrations of biochar leacheates (between 3% and 10% by weight). Results also show that the organic molecules in biochar leacheates enhance the cold resistance of plants when other interference factors are excluded. We suggest that the positive influence of biochar on plant cold tolerance is because of surface organic molecules which likely function by entering a plant and interacting with stress-related proteins. Thus, to verify these mechanisms, this study used gas chromatography-mass spectrometry (GC-MS) techniques, identifying 20 organic molecules in biochar extracts using the National Institute of Standards and Technology (NIST) library. Further, to illustrate how these organic molecules work, we utilized the molecular docking software Autodock to show that the organic molecule 6-(Methylthio)hexa-1,5-dien-3-ol from biochar extracts can dock with the stress-related protein zinc-dependent activator protein (ZAP1). 6-(Methylthio)hexa-1,5-dien-3-ol has a similar binding mode with the ligand succinic acid of ZAP1. It can be inferred that the organic molecule identified in this study performs the same function as the ZAP1 ligand, stimulating ZAP1 driving cold-resistant functions, and enhancing plant cold tolerance. We conclude that biochar treatment enhances cold tolerance in rice seedlings via interactions between organic molecules and stress related proteins.